Applications of mesenchymal stem cell technology in bovine species - Trindade Hill, Amanda Baracho [UNESP]; Bressan, Fabiana Fernandes; Murphy, Bruce D.; Garcia, Joaquim Mansano [UNESP] (Bmc, 2019)
Mesenchymal stem cells (MSCs) have received a great deal of attention over the past 20years mainly because of the results that showed regeneration potential and plasticity that were much stronger than expected in prior decades. Recent findings in this field have contributed to progress in the establishment of cell differentiation methods, which have made stem cell therapy more clinically attractive. In addition, MSCs are easy to isolate and have anti-inflammatory and angiogenic capabilities. The use of stem cell therapy is currently supported by scientific literature in the treatment of several animal health conditions. MSC may be administered for autologous or allogenic therapy following either a fresh isolation or a thawing of a previously frozen culture. Despite the fact that MSCs have been widely used for the treatment of companion and sport animals, little is known about their clinical and biotechnological potential in the economically relevant livestock industry. This review focuses on describing the key characteristics of potential applications of MSC therapy in livestock production and explores the themes such as the concept, culture, and characterization of mesenchymal stem cells; bovine mesenchymal stem cell isolation; applications and perspectives on commercial interests and farm relevance of MSC in bovine species; and applications in translational research.
Keywords: Mesenchymal stem cells; Cell culture; Pluripotent; Livestock; Cow; Cattle; Biotechnology; Cellular therapy; Regenerative medicine; Translational research